PEMBUKTIAN KASUS HUKUM WARIS DALAM SENGKETA PEMBAGIAN WARISAN EKA TJIPTA WIDJAJA: STUDI KASUS PUTUSAN NO.301/PDT.G/2020/PN JKT.PST - Aaron William Pantow; Chionya Sherly Mahat; George Vitto Corleone Sitorus; Grace Margareth Simarmata; Jessica Gabriela Chandra Gunawan; Keren Angeline Manoppo (JURNAL ILMIAH NUSANTARA, 2024)
The inheritance dispute within Eka Tjipta Widjaja's family reveals fundamental challenges in the application of inheritance law in Indonesia, particularly concerning equity in asset distribution and the recognition of inheritance rights for children born out of wedlock. Freddy Widjaja, as an illegitimate child, received a significantly smaller portion compared to other heirs, raising issues of inequality in inheritance distribution. Additionally, the validity of the 2008 will has been questioned due to its lack of detailed asset allocation, impacting legal certainty and increasing the potential for disputes among heirs. This study analyzes the implications of Constitutional Court Decision No. 46/PUU-VIII/2010, which grants civil rights to children born out of wedlock, and highlights the need for legal reform to ensure more equitable protection for all heirs. Recommendations include drafting wills with greater transparency and fairness and promoting equitable asset distribution in large family estates to prevent future disputes.